2018
DOI: 10.1002/14651858.cd004363.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressants for preventing postnatal depression

Abstract: Due to the limitations of the current evidence base, such as the low statistical power of the included studies, it is not possible to draw any clear conclusions about the effectiveness of antidepressants for the prevention of postnatal depression. It is striking that no new eligible trials have been completed in the period of over a decade since the last published version of this review. Larger trials are needed which include comparisons of antidepressant drugs with other prophylactic treatments (e.g. psycholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 33 publications
0
47
0
7
Order By: Relevance
“…[86][87][88][89]. A recent Cochrane review concluded that further studies with greater numbers of participants are necessary in order to make any conclusions about the effectiveness of antidepressants for the prevention of PPD [90].…”
Section: Prophylactic Treatmentmentioning
confidence: 99%
“…[86][87][88][89]. A recent Cochrane review concluded that further studies with greater numbers of participants are necessary in order to make any conclusions about the effectiveness of antidepressants for the prevention of PPD [90].…”
Section: Prophylactic Treatmentmentioning
confidence: 99%
“…The studies which investigated antidepressants found that sertraline was more likely to exhibit preventative effects in developing postpartum depression and reduce the extent of depressive symptoms in the postpartum period. These studies found that sertraline was more effective in reducing the risk of developing postpartum depression and experiencing postpartum depressive symptoms compared to nortriptyline (Howard et al, 2005;Molyneaux et al, 2018;Pariser, Nasrallah, & Gardner, 1997). Other studies compared sertraline with a placebo in treating postpartum depression.…”
Section: Analysis Of Resultsmentioning
confidence: 99%
“…International Publications. 20 As there is no absolute contraindication to taking antidepressant medications during pregnancy, they should not be stopped abruptly, which would increase the risk of depression relapse with a rebound effect. 21,22 In France in 2016, 5% of women were exposed to at least one anxiolytic-hypnotic drug during pregnancy.…”
Section: And the 2018 International Cochrane Reviewmentioning
confidence: 99%